2021
DOI: 10.1112/s0010437x2100734x
|View full text |Cite
|
Sign up to set email alerts
|

Canonical bases arising from quantum symmetric pairs of Kac–Moody type

Abstract: For quantum symmetric pairs $(\textbf {U}, \textbf {U}^\imath )$ of Kac–Moody type, we construct $\imath$ -canonical bases for the highest weight integrable $\textbf U$ -modules and their tensor products regarded as $\textbf {U}^\imath$ -modules, as well as an $\imath$ -canonical basis for the modified form of the $\imath$ -quantum group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…One may hope that these new braid group symmetries preserve the integral Z[q, q −1 ]form on (modified) ıquantum groups in [BW18b,BW21]. (This will be highly nontrivial to verify, as the ıdivided powers are much more sophisticated than the divided powers.)…”
Section: ) the Symmetries T ′mentioning
confidence: 99%
“…One may hope that these new braid group symmetries preserve the integral Z[q, q −1 ]form on (modified) ıquantum groups in [BW18b,BW21]. (This will be highly nontrivial to verify, as the ıdivided powers are much more sophisticated than the divided powers.)…”
Section: ) the Symmetries T ′mentioning
confidence: 99%
“…of cyclotomic Birman-Murakami-Wenzl algebras and cyclotomic Nazarov-Wenzl algebras over the complex field C to the Kazhdan-Lusztig theory (ı-canonical basis, etc.) of certain g ♯ -modules studied in [6][7][8][9][10]. This is a project in progress.…”
Section: Introductionmentioning
confidence: 96%
“…In recent years, Bao and Wang have generalized Lusztig's approach on canonical bases in [Lu94] and developed a general theory of the canonical basis for ıquantum groups arising from quantum symmetric pairs of arbitrary finite type in [BW18b] and of Kac-Moody type in [BW21]. They showed that any based module of a quantum group of finite type (cf.…”
Section: Introductionmentioning
confidence: 99%